2018
DOI: 10.1017/s1368980018001386
|View full text |Cite
|
Sign up to set email alerts
|

Water intake from foods and beverages and risk of mortality from CVD: the Japan Collaborative Cohort (JACC) Study

Abstract: Higher intake of fluids from foods and beverages was associated with reduced risk of cardiovascular mortality in both sexes and reduced risk of ischaemic stroke in women in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 29 publications
0
26
0
2
Order By: Relevance
“…Evidence for calcium remains unclear. In some papers (Jang et al, 2016) authors found out no statistically signifi cant association between water intake and any CVD diseases, in other (Cui et al, 2018) -they did. Problem of infl uence of heavy metals in water were discussed in (Alissa & Ferns, 2011;Chowdhury et al, 2018;Rehman, Fatima, Waheed & Akash, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Evidence for calcium remains unclear. In some papers (Jang et al, 2016) authors found out no statistically signifi cant association between water intake and any CVD diseases, in other (Cui et al, 2018) -they did. Problem of infl uence of heavy metals in water were discussed in (Alissa & Ferns, 2011;Chowdhury et al, 2018;Rehman, Fatima, Waheed & Akash, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…The question of connection between consumed water quality and public health was discussed and investigated in numerous research (Monarca, Zerbini, Simonati & Gelatti, 2003;Catling, Abubakar, Lake, Swift & Hunter, 2008;Jang et al 2016;Cui, Iso, Eshak, Maruyama & Tamakoshi, 2018). Authors of the study (Catling et al, 2008) found significant evidence of an inverse association between magnesium levels in drinking water and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…While total water intake from foods and beverages was associated with a lower risk of mortality in some investigations [14] others failed to find such evidence [15,16] . No information is available about the strength and shape of dose-response relation between water intake and risk of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to most developed countries, the event risks of cerebrovascular diseases are high and it remains one of top-ranked causes of death and disability in Japan [1,2]. Recent studies demonstrated that patients with cerebral infarction (CI) took less water before the onset than healthy subjects [3], and higher water intake reduced mortality due to ischemic stroke [4,5,6,7,8]. The potential association between water intake and CI is generally explained via the following pathophysiological mechanism; 1) insufficient hydration is one of the most important factors causing dehydration and 2) dehydration is considered to be associated with the development of cerebral ischemic events [7,9,10], probably because of vascular collapse [11], increased blood viscosity [12], and spasm [13].…”
Section: Introductionmentioning
confidence: 99%